Ammonia adsorption catalyst and its manufacturing method and application
By using precious metal-zeolite adsorption materials in ASCs, the existing ASCs are solved, and the problems of low efficiency, high cost and poor flexibility are achieved, efficient ammonia adsorption and oxidation are achieved, production costs are reduced, and thermal stability and application flexibility are improved.
Patent Information
- Application Number
- JP2023513253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-01
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-09-01
Smart Images

Figure 0007650959000002 
Figure 0007650959000003 
Figure 0007650959000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of engine exhaust treatment catalysts, specifically to an ammonia adsorption catalyst and its manufacturing method and application. [Background technology]
[0002] Ammonia (NH3) in automobile engine exhaust aftertreatment systems comes from two sources: (1) it is generated over catalysts (e.g., three-way catalysts (TWC) and lean-burn nitrogen oxide trap catalysts (LNT)) under rich operating conditions, and (2) it is actively added externally to the aftertreatment system as a reductant for lean-burn selective catalytic reduction (SCR). The basic function of an ammonia oxidation catalyst (ASC) is to adsorb and remove (including conversion or oxidation) excess ammonia (NH3) in the exhaust gas to reduce ammonia leakage with the exhaust. Typically, the ASC catalyst is located at the rear end of the aftertreatment system. Currently, ASC products on the market generally have two independent coating layers, one is an ammonia oxidation coating layer (e.g., ammonia oxidation layer 2 in FIG. 1) located on the surface of the carrier 3, and one is an ammonia adsorption material layer (e.g., adsorption layer 1 in FIG. 1) located on the surface of the ammonia oxidation coating layer. As shown in FIG. 1, an ammonia-containing airflow f passes through the ASC and is first adsorbed by the front adsorption layer 1. The adsorbed ammonia is gradually desorbed according to the flow of the engine exhaust. The desorbed ammonia quickly passes through the ammonia oxidation layer 2 and is at least partially oxidized (in this process, the ammonia that is not adsorbed and not oxidized continues the adsorption, desorption and oxidation process by the downstream adsorption layer and ammonia oxidation layer).
[0003] Here, the representative ammonia adsorption material for forming the ammonia adsorption material layer is a metal ion exchanged zeolite material (e.g., Cu-β, Fe-β, Cu-SSZ-13, etc.), and such a zeolite material, in addition to adsorbing ammonia, also gradually consumes ammonia as a reducing agent to convert NOx under the condition of lean combustion (air-fuel ratio λ>1.0), and it mainly adsorbs ammonia in exhaust gas by two methods, namely chemical adsorption and physical adsorption. Chemically adsorbed ammonia is relatively stable and difficult to desorb, but the amount of chemically adsorbed is finite (chemical adsorption mainly occurs at the Bronsted acid sites (BAS) in zeolite, and the amount of chemically adsorbed ammonia is generally less than 15% of the total ammonia adsorption amount. When the catalyst is exposed to normal heat aging temperatures (generally about 650-700 ° C, especially > 700 ° C), the BAS acid sites become extremely few, thereby significantly reducing the amount of chemical adsorption of ammonia by the adsorption material). A large amount of ammonia in the exhaust gas is temporarily physically adsorbed in the zeolite due to the van der Waals force in the zeolite, the ammonia adsorbed in the zeolite is gradually desorbed according to the flow of the engine exhaust gas, and the ammonia desorbed from the tip zeolite is re-adsorbed and desorbed by the downstream zeolite, and is repeatedly circulated. The ammonia oxidation material in the ammonia oxidation layer generally includes a substrate such as alumina and a precious metal (e.g., platinum (Pt)) supported on the substrate, and after ammonia is desorbed from the zeolite material in the adsorption layer, it quickly passes through the ammonia oxidation layer and is at least partially oxidized, and the unoxidized ammonia continues the adsorption, desorption and oxidation process by the downstream adsorption layer and ammonia oxidation layer.
[0004] At present, in order to reduce ammonia leakage in aftertreatment systems, ASC has been widely applied in selective catalytic reduction (SCR) systems under lean burn operating conditions, and in the rear end of three-way catalysts (TWCs) in natural gas (including compressed natural gas (CNG) and liquefied natural gas (LNG)) engine operating systems under stoichiometric air-fuel ratio (λ=0.98-1.02) operating conditions. Specifically, under lean burn (oxygen enriched) operating conditions, NOx in the exhaust gas can generally be removed by SCR, specifically, urea is injected, the urea is hydrolyzed into ammonia, and the ammonia is selectively reduced to nitrogen gas and water, and the rear end of the SCR can remove the excess ammonia that is about to leak by ASC. In this lean burn state, ammonia is mainly removed by the ASC in three ways: (1) catalytic oxidation by the ammonia oxidation layer, (2) as a reducing agent to convert NOx in the zeolite material, and partially consumed by it, and (3) at high temperature, a small part of the ammonia is oxidized to nitrogen gas, etc. in the zeolite material. The working principle of the ASC in the stoichiometric engine TWC aftertreatment system is as follows: unlike the active introduction of ammonia (urea injection) in the lean burn engine SCR aftertreatment system, the ammonia generated in the TWC is only generated under rich (lambda<1.0) conditions and adsorbed by the downstream ASC (the adsorbed ammonia cannot be oxidized or removed under rich conditions), and when the exhaust is switched to a lean (lambda>1.0) state (including engine operation modes such as fuel cut), the ammonia is mainly oxidized in the oxidation layer under oxygen-rich conditions, and the more the ASC adsorbs ammonia, the higher the oxidation efficiency and the higher the ability to reduce ammonia leakage in the stoichiometric engine exhaust.
[0005] As mentioned above, the current representative ASC catalyst consists of a surface adsorption layer and a lower ammonia oxidation layer (shown in FIG. 1). In order to improve the efficiency of ASC in reducing ammonia leakage, the amount of ammonia adsorption material needs to be as large as possible. Therefore, the amount of adsorption layer in ASC generally reaches 150 g / L catalyst carrier or more, and the amount of ammonia oxidation layer is 50 g / L carrier or less. Current ASC generally has the following shortcomings: (1) even if the total coating amount is 200 g / L carrier or more, the ammonia adsorption amount of ASC is still insufficient, and the adsorption efficiency is low; (2) the oxidation of ammonia is mainly completed by the ammonia oxidation layer in the short time between the time when ammonia is desorbed from the zeolite material and the time when it is adsorbed by the zeolite material, the reaction time is short, and the conversion efficiency is limited; (3) a certain combination of the adsorption layer and the ammonia oxidation layer determines that the ASC must be applied independently (adopting a carrier or compartment coating different from other catalysts), thus increasing the cost of the carrier, package, etc. of the aftertreatment system, and may also bring difficulties to the rational arrangement of the limited chassis space.
[0006] Reducing ammonia leakage from engine exhaust has already been given importance in fields including environmental protection and vehicle maintenance enterprises, and the more stringent EU7 / CN7 emission standards are expected to emerge around 2026. The application of ASC to reduce ammonia leakage from engine exhaust has already become an important option, but how to further improve the efficiency of ASC, reduce the product costs of ASC, and increase the application flexibility of ASC remain technical problems to be solved by those skilled in the art. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides an ammonia adsorption catalyst, which has the advantages of high ammonia adsorption / conversion efficiency, low cost, flexible application and so on, and can effectively improve the shortcomings of the prior art. [Means for solving the problem]
[0008] An ammonia adsorption catalyst provided by one aspect of the present invention includes a support and an adsorption layer located on a surface of the support, the adsorption layer including a zeolite adsorption material containing a precious metal.
[0009] According to one embodiment of the invention, the precious metal comprises platinum and / or palladium.
[0010] According to one embodiment of the present invention, the precious metal in the zeolite adsorbent material containing the precious metal and the mass / volume ratio of the carrier is between 1 and 20 grams per cubic foot.
[0011] According to one embodiment of the present invention, the zeolite adsorption material containing precious metals is obtained by exchanging precious metals with zeolite through an ion exchange method, and the zeolite includes at least one of β zeolite, Y zeolite, and ZSM-5 zeolite.
[0012] According to one embodiment of the present invention, the mass content of the noble metal-containing zeolite adsorption material in the adsorption layer is 90-100%.
[0013] According to one embodiment of the present invention, the mass / volume ratio of the zeolite adsorption material containing a precious metal to the carrier is 30-200 g:1 L.
[0014] According to one embodiment of the present invention, the support includes at least one of cordierite, silicon carbide, and a metal support.
[0015] A method for producing the ammonia adsorption catalyst provided by another aspect of the present invention includes the steps of: performing ion exchange treatment on zeolite using a precious metal precursor to obtain a zeolite adsorption material containing a precious metal; mixing the zeolite adsorption material containing a precious metal with an adhesive and a solvent to produce a slurry; and coating the slurry on a carrier, drying and firing the carrier to form an adsorption layer, thereby obtaining the ammonia adsorption catalyst.
[0016] Yet another aspect of the present invention provides the application of the above-described ammonia adsorption catalyst in an engine aftertreatment system.
[0017] According to one embodiment of the present invention, the engine aftertreatment system includes a stoichiometric engine aftertreatment system.
[0018] According to one embodiment of the present invention, the engine aftertreatment system includes a three-way catalyst, and the gas to be treated in the engine aftertreatment system is first treated by the three-way catalyst and then treated by the ammonia adsorption catalyst, or the engine aftertreatment system includes a selective catalytic reduction catalyst, and the gas to be treated in the engine aftertreatment system is first treated by the selective catalytic reduction catalyst and then treated by the ammonia adsorption catalyst.
[0019] According to one embodiment of the present invention, the ammonia adsorption catalyst is used in combination with a three-way catalyst, and the preparation method includes at least one of the following methods A and B: Method A: a three-way catalyst layer made of a three-way catalyst is provided between the adsorption layer of the ammonia adsorption catalyst and the carrier; Method B: the adsorption layer of the ammonia adsorption catalyst further contains the three-way catalyst. Effect of the Invention
[0020] In the present invention, precious metal is introduced into the zeolite adsorption material, and there is no need to further coat the carrier with an ammonia oxidation layer. This simplifies the manufacturing process of the catalyst, reduces the manufacturing difficulty, reduces costs, and saves space. More zeolite adsorption material can be supported on the carrier, increasing the adsorption amount of ammonia. The ammonia adsorbed in the zeolite adsorption material can be directly catalytically oxidized in the zeolite adsorption material, which can extend the reaction time of ammonia oxidation and thereby improve the conversion rate of ammonia. In addition, the ammonia adsorption catalyst of the present invention can also have other functions. It can also be used in combination with the catalyst of the present invention (for example, it can be used in combination with a coating layer of a three-way catalyst (TWC) to adsorb ammonia when the exhaust gas is rich (λ<1.0) and oxidize ammonia when the exhaust gas is lean (λ>1.0)), making its application more flexible. In addition, research has shown that, compared with the conventional zeolites with other metal atom substitutions (such as Cu-zeolite) and hydrogen-type zeolites (H-zeolites), the present invention is a zeolite adsorption material with a noble metal introduced into it (the noble metal substituted in the zeolite is the Bronsted acid site H in the zeolite). + (replaces) can not only increase the ammonia adsorption amount, but also show better thermal stability and relatively good ammonia adsorption performance at heat aging temperature (650-750°C), the heat aging temperature is generally higher than the actual application temperature, and the temperature in the catalyst application process is generally 200-500°C, the ammonia adsorption catalyst of the present invention can be used at 200-500°C and even higher temperatures. Therefore, the ammonia adsorption catalyst of the present invention has the advantages of high ammonia adsorption / conversion efficiency, low cost, flexible application, excellent thermal stability, etc., which is of great significance for actual industrial application. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram of the structure and application process of a conventional ASC. [Diagram 2] 2 is a graph showing the change in ammonia adsorption capacity with temperature of ammonia adsorption catalysts ASC having different zeolite loadings similar to each other after fresh and aging in one embodiment of the present invention; [Diagram 3] 1 is a graph showing the change in ammonia conversion efficiency with temperature under lean burn conditions of an ammonia adsorption catalyst in an embodiment of the present invention and an ASC in a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] In order to allow those skilled in the art to better understand the aspects of the present invention, the present invention will be described in more detail below. The specific embodiments given below are only for illustrating the principles and features of the present invention, and the given examples are only used to interpret the present invention, and do not limit the scope of the present invention. Based on the examples of the present invention, all other embodiments obtained by those skilled in the art without creative labor are all within the protection scope of the present invention.
[0023] The ammonia adsorption catalyst of the present invention comprises a support and an adsorption layer located on the surface of the support, the adsorption layer comprising a zeolite adsorption material containing a precious metal.
[0024] In the present invention, the zeolite adsorption material has good adsorption and catalytic oxidation ability for ammonia, wherein the precious metal introduced into the zeolite adsorption material mainly plays the function of catalytic oxidation ammonia, such as, but not limited to, at least one of platinum (Pt), palladium (Pd) and rhodium (Rh), in some preferred embodiments, the precious metal includes platinum and / or palladium, which is advantageous to further improve the efficiency of adsorption catalytic oxidation of ammonia and save costs.
[0025] Comparatively speaking, For the volume of coating catalyst or support If the content of the precious metal is too high, the cost will be high, and if the content of the precious metal is too low, the adsorption and conversion performance of the ammonia adsorption catalyst will be affected to some extent. Therefore, taking these factors into consideration, the content of the precious metal in the zeolite adsorption material containing the precious metal is generally set to 1 to 20 g / ft3. Carrier , e.g. 1, 3, 5, 7, 10, 12, 15, 18, 20 grams per cubic foot Carrieror any two of the above, and generally, the range is preferably 3 to 5 grams per cubic foot. Carrier It is.
[0026] In the present invention, the above-mentioned zeolite adsorption material containing precious metals may be obtained by exchanging precious metals into zeolite by ion exchange method, and in some embodiments, the zeolite used includes at least one of beta zeolite, Y zeolite, and ZSM-5, where the volume of the zeolite adsorption material is essentially equal to the volume of the zeolite used, and the content of precious metals is 3-5 grams / cubic foot. Carrier In order to obtain a zeolite adsorption material having a molecular weight of 1.0 or less, the manufacturing process of the zeolite adsorption material includes: Precious metals in zeolites Use 3-5 grams per cubic foot Carrier It is to be understood that the present invention is not limited to the ion exchange method, and the precious metal may be exchanged with the zeolite by a spray method or the like.
[0027] Specifically, the ion exchange process generally involves dissolving a precious metal precursor in a solvent to form an immersion liquid, immersing a zeolite in the immersion liquid, for example by equal volume immersion, and then drying and calcining to produce a zeolite adsorption material containing a precious metal, where the precious metal precursor generally may include a compound containing a precious metal such as a salt of a precious metal, and specifically may include a soluble salt of a precious metal such as a nitrate salt, for example platinum nitrate and / or palladium nitrate, and anions such as nitrate radicals are decomposed and released from the zeolite material during drying and calcination.
[0028] In general, the adsorption layer further contains an adhesive and / or an auxiliary (auxiliary material), which is advantageous for adhering the precious metal-containing zeolite adsorption material to form a coating layer (i.e., adsorption layer) and optimizes the performance of the adsorption layer, such as strength and stability, and in some embodiments, the mass content of the precious metal-containing zeolite adsorption material in the adsorption layer is 90-100%, with the remainder being the adhesive and auxiliary material. Optionally, the adhesive may include aluminum paste and / or silica gel, and the auxiliary may include cerium material and / or zirconium material.
[0029] Specifically, the adsorption layer may be formed by coating the surface of a carrier with a zeolite adsorption material containing the above-mentioned precious metal. In a specific implementation, the zeolite adsorption material may be mixed with an adhesive and a solvent to prepare a slurry, which may then be coated on the surface of a carrier and dried to form an adsorption layer.
[0030] Further research has revealed that the mass volume ratio of the zeolite adsorption material containing the noble metal to the carrier is 30 to 280 g: 1 L, for example, 30 g: 1 L, 50 g: 1 L, 80 g: 1 L, 100 g: 1 L, 120 g: 1 L, 150 g: 1 L, 180 g: 1 L, 200 g: 1 L, 230 g: 1 L, 250 g: 1 L, 280 g: 1 L, or any two ratios thereof. In a specific implementation, the thickness of the adsorption layer (the amount of the zeolite adsorption material coated on the carrier) may be controlled according to the chassis space of the automobile, and as much zeolite adsorption material as possible can be coated to increase the amount of ammonia adsorption. In general, the ratio of the mass of the adsorption layer to the volume of the carrier is preferably 150 g to 230 g: 1 L.
[0031] The present invention can use a carrier conventional in the art, and in some preferred embodiments, the carrier includes at least one of cordierite (generally in the form of a ceramic honeycomb), silicon carbide, and metal carriers. The structure of the carrier can be, for example: gasoline The present invention is not particularly limited to this.
[0032] The method for producing an ammonia adsorption catalyst provided by the present invention includes the steps of: performing ion exchange treatment on zeolite using a precious metal precursor (i.e., exchanging precious metal with zeolite by ion exchange method) to obtain a zeolite adsorption material containing precious metal; mixing the zeolite adsorption material containing precious metal with an adhesive and a solvent to produce a slurry; coating the slurry on the surface of a carrier, drying at 80-90°C to remove a large amount of solvent, then drying at 100-200°C to remove the remaining solvent, and subsequently firing at 500-650°C to form an adsorption layer on the surface of the carrier, thereby obtaining an ammonia adsorption catalyst; wherein the firing time may be, but is not limited to, 1-2 hours.
[0033] In the present invention, the above-mentioned ammonia adsorption catalyst can be used directly, or can be mixed with other catalysts or their functional components. For example, the above-mentioned ammonia adsorption catalyst can be combined with TWC to form a multi-functional catalyst. Specifically, TWC is introduced into the adsorption layer, that is, a zeolite adsorption material containing precious metal is mixed with TWC to form an adsorption layer, that is, the above-mentioned adsorption layer further contains TWC catalyst; or, in addition to the adsorption layer, a TWC coating layer made of TWC can be further provided on the surface of the carrier, and the adsorption layer and the TWC coating layer are located in different regions on the surface of the carrier (i.e., are provided in a partitioned manner on the surface of the carrier), and the two may be in contact or not in contact (i.e., are separated by a certain distance); or, the TWC coating layer and the adsorption layer are provided hierarchically on the surface of the carrier, and the TWC coating layer is located between the surface of the carrier and the adsorption layer, or the adsorption layer is located between the TWC coating layer and the surface of the carrier, and preferably, the adsorption layer is located between the TWC coating layer and the surface of the carrier.
[0034] The present invention further provides an application of the above-mentioned ammonia adsorption catalyst in an engine aftertreatment system, which may include a stoichiometric engine aftertreatment system, i.e., the above-mentioned ammonia adsorption catalyst may be used in a stoichiometric engine aftertreatment system, for example, at the rear end of the TWC of a stoichiometric engine aftertreatment system (i.e., the engine exhaust is first treated by the TWC and then the ammonia adsorption catalyst is applied to the rear end of the TWC of the stoichiometric engine aftertreatment system, i.e., the engine exhaust is first treated by the TWC and then the ammonia adsorption catalyst is applied to the rear end of the TWC of the stoichiometric engine aftertreatment system, in The ammonia adsorption catalyst may be used in the process of stoichiometric air-fuel ratio operation (processing), and can efficiently adsorb the converted ammonia. Here, the stoichiometric air-fuel ratio operation of the engine is completed with the air-fuel ratio (λ) fluctuating slightly up and down around the stoichiometric air-fuel ratio (λ=1.0) (i.e., in the engine operation process, fuel such as natural gas is burned in a combustion mode with an almost stoichiometric air-fuel ratio), and the air-fuel ratio of the stoichiometric air-fuel ratio operation engine is generally 0.98-1.02 (i.e., λ=0.98-1.02). Generally, in the specific application process of the engine stoichiometric air-fuel ratio operation, under rich (λ<1.0) conditions, ammonia is generated on the TWC, and due to the low oxygen content, the ammonia adsorption catalyst can hardly oxidize ammonia, and mainly adsorbs ammonia; under lean (λ>1.0) conditions, ammonia is no longer generated on the TWC, and the ammonia adsorption catalyst can oxidize ammonia, and mainly oxidizes ammonia.
[0035] The ammonia adsorption catalyst of the present invention can be used in a stoichiometric engine aftertreatment system, which can significantly improve the ammonia adsorption amount and show good conversion (catalytic oxidation) performance for ammonia. However, it is not limited to the stoichiometric engine aftertreatment system, and the engine aftertreatment system can further include a lean-burn (λ>1.0) engine aftertreatment system, that is, the ammonia adsorption catalyst can be used in a lean-burn engine aftertreatment system, for example, in the rear end of SCR in a lean-burn engine aftertreatment system.
[0036] Specifically, the ammonia adsorption catalyst may be used alone, and in some embodiments, the engine aftertreatment system includes a three-way catalyst (TWC), and the gas to be treated (exhaust) in the engine aftertreatment system is first treated by the three-way catalyst and then treated by the ammonia adsorption catalyst, i.e., the ammonia adsorption catalyst is used at the rear end of the TWC. In other embodiments, the engine aftertreatment system includes a selective catalytic reduction (SCR) catalyst, and the gas to be treated in the engine aftertreatment system is first treated by the selective catalytic reduction catalyst and then treated by the ammonia adsorption catalyst, i.e., the ammonia adsorption catalyst is used at the rear end of the SCR catalyst.
[0037] The application of the present invention is not limited to the above method, and the ammonia adsorption catalyst may be combined with other catalysts (such as TWC) or their functional components. For example, in some embodiments, the ammonia adsorption catalyst is used in combination with a three-way catalyst, and the preparation method includes at least one of the following methods A and B: Method A: a three-way catalyst layer made of a three-way catalyst is provided between the adsorption layer of the ammonia adsorption catalyst and the support; Method B: the adsorption layer of the ammonia adsorption catalyst further contains the three-way catalyst. The ammonia adsorption catalyst Specifically, it may be used in a TWC system in an engine aftertreatment system.
[0038] In order to make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention are described below in combination with specific examples, and it is obvious that the described examples are only a part of the embodiments of the present invention, and are not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative labor belong to the protection scope of the present invention. Example 1
[0039] The ammonia adsorption catalyst of this embodiment (referred to as "fresh (Pt-zeolite)") comprises a carrier, an alumina coating layer located on the surface of the carrier, and an adsorption layer located on the surface of the alumina coating layer, where the alumina coating layer is formed by coating an alumina material with an adhesive, and the adsorption layer is formed by coating a zeolite adsorption material (Pt-zeolite) containing platinum with an adhesive; The components of the adsorption layer are an adhesive and a platinum-containing zeolite adsorption material (Pt-zeolite), the mass content of the Pt-zeolite in the adsorption layer is 97%, and the remainder is the adhesive; Pt-zeolite with platinum content of 5 grams per cubic foot Carrier and Pt-zeolite is obtained by exchanging platinum for zeolite by ion exchange method, and the zeolite used is β-zeolite. The mass / volume ratio of Pt-zeolite to the carrier is 150 g:1 L (i.e., the loading amount of Pt-zeolite is 150 g / L); The mass volume ratio of the alumina coating layer to the carrier is 50g:1L (i.e., the loading amount of alumina is 50g / L); The support is cordierite. Example 2
[0040] The differences between Example 2 and Example 1 are as follows: the ammonia adsorption catalyst is composed of a carrier and an adsorption layer located on the surface of the carrier (i.e., no alumina coating layer), and the mass volume ratio of Pt-zeolite to the carrier is 200g:1L (i.e., the loading amount of Pt-zeolite is 200g / L). Comparative Example 1
[0041] The catalyst of Comparative Example 1 (referred to as "fresh (Cu-zeolite)") is a conventional ASC, and is made up of a support, an ammonia oxidation layer located on the surface of the support, and an ammonia OxidationThe ammonia adsorption layer is a coating layer formed by coating Cu-zeolite with an adhesive, and the ammonia oxidation layer is a coating layer (50 g / L) formed by coating an alumina material carrying platinum with an adhesive. do. The carrier in Comparative Example 1 is the same as that in Example 1. The platinum content in the total coating layer consisting of the ammonia adsorption layer and the ammonia oxidation layer in Comparative Example 1 is the same as the platinum content in the adsorption layer in Example 1; The loading amount of Cu-zeolite in Comparative Example 1 is the same as the loading amount of Pd-zeolite in Example 1 (150 g / L). Comparative Example 2
[0042] The difference between the catalyst of Comparative Example 2 (referred to as fresh (H-zeolite)) and Comparative Example 1 is that H-zeolite is used to replace Cu-zeolite, and other conditions are the same as those of Comparative Example 1. (Catalyst performance test)
[0043] 1, catalyst aging The ammonia adsorption catalyst in Example 1 was placed in a tubular reactor at 720°C and a space velocity of 30,000 h -1 The reaction was continued for 40 hours under the above conditions to obtain an aged ammonia adsorption catalyst (referred to as aged (Pt-zeolite)). According to the above aging process, the catalyst in Comparative Example 1 is aged to obtain an aged catalyst (referred to as aged (Cu-zeolite)), According to the above aging process, the catalyst in Comparative Example 2 is aged to obtain the aged catalyst (denoted as aged (H-zeolite)). 2. Testing Fresh (Pt-zeolite), Fresh (Cu-zeolite), Fresh (H-zeolite), Aged (Pt-zeolite), Aged (Cu-zeolite), Aged (The following Test 1 and Test 2 are carried out by using the H-zeolite catalyst, respectively, and the change curve of the ammonia adsorption amount with temperature under the theoretical air-fuel ratio operating condition (shown in FIG. 2) and the change curve of the ammonia conversion rate with temperature under the lean burn operating condition (shown in FIG. 3) are measured. Test 1: The exhaust gas components after the TWC of the engine aftertreatment system operated at a stoichiometric air-fuel ratio (shown in Table 1 for the ammonia adsorption experiment syngas) were simulated at a space velocity of 170,000 h -1 Under these conditions, the change curve of the ammonia adsorption amount (storage amount) of the catalyst according to temperature is tested. Test 2: The exhaust gas components after SCR of a lean-burn engine aftertreatment system (shown in Table 1 for the ammonia oxidation experiment syngas) were simulated at a space velocity of 170,000 h -1 Under the above conditions, the change curve of the efficiency of catalytic conversion of ammonia (ammonia conversion rate) as a function of temperature is tested.
[0044] [Table 1]
[0045] As can be seen from FIG. 2, the ammonia adsorption amount of the catalyst decreases with increasing temperature. The ammonia adsorption amount of the fresh (Pd-zeolite) is 2.79 g / L at 200°C and 0.65 g / L at 500°C. Aging also affects the ammonia adsorption performance of the catalyst. The ammonia adsorption amount of the aged (Pd-zeolite) at 200°C is about 1.36 g / L. In addition, whether fresh or aged, the ammonia adsorption amount of the ammonia adsorption catalyst of Example 1 is higher than that of the catalysts of Comparative Example 1 and Comparative Example 2, showing better ammonia adsorption performance and thermal stability. The ammonia adsorption amounts of the fresh (Pt-zeolite), fresh (Cu-zeolite), and fresh (H-zeolite) at 200°C are 2.79 g / L, 2.4 g / L, and 2.3 g / L, respectively. The ammonia adsorption amount of the aged (Pt-zeolite), aged (Cu-zeolite), and aged (H-zeolite) is 2.79 g / L, 2.4 g / L, and 2.3 g / L, respectively. ( The ammonia adsorption amounts of H-zeolite at 200°C are 1.36 g / L, 0.9 g / L, and 0.67 g / L, respectively.
[0046] As can be seen in combination with FIG. 3, the ammonia adsorption catalyst of Example 1 has an increased ammonia adsorption amount and a good ammonia conversion performance, which is higher than that of Comparative Example 1. To The ammonia conversion rate of the catalyst at 1000°C is close to that at 1000°C, and the ammonia conversion rate of the catalyst tends to increase with increasing temperature. Although the ammonia conversion performance of the catalyst decreases after aging, the aged (Pt-zeolite) can still maintain a higher ammonia conversion rate.
[0047] In general, the process of removing ammonia from the exhaust gas of an engine operating at a stoichiometric air-fuel ratio can be divided into two relatively independent and short processes: ammonia is generated during rich combustion and is adsorbed by a catalyst such as ASC, and ammonia is oxidized during lean combustion. As described above, the catalytic oxidation efficiency of ammonia by the ammonia adsorption catalyst of Example 1 is almost the same as that of the catalysts in Comparative Examples 1 and 2, the ammonia adsorption amount of the ammonia adsorption catalyst of Example 1 is significantly better than that of the catalysts in Comparative Examples 1 and 2, and the ammonia adsorption catalyst of Example 1 can be coated with up to 30% more ammonia adsorption (zeolite) material than Comparative Examples 1 and 2 when the carrier size is the same. When the catalytic oxidation efficiency of ammonia is almost the same, the larger the ammonia adsorption amount, the better the removal effect of ammonia in the exhaust gas.
[0048] In the present invention, the above Example 1 is designed to reduce the influence of variables as much as possible, and the relevant experimental processes of Example 1 and Comparative Example 1 are listed, which proves that the ammonia adsorption catalyst of the present invention has a superior ammonia reduction effect compared to conventional ASC. The present invention further designs Example 2, and the above-mentioned experiments are carried out on the catalyst of Example 2. As a result, it is shown that the ammonia adsorption performance, ammonia oxidation performance, thermal stability and other performances of Example 2 are all superior to those of the ammonia adsorption catalyst of Example 1.
[0049] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application should be included within the protection scope of the present application. [Explanation of symbols]
[0050] 1...adsorption layer, 2...ammonia oxidation layer, 3...support, f...air flow.
Claims
1. An ammonia adsorption catalyst comprising: a carrier; and an adsorption layer located on a surface of the carrier, the adsorption layer comprising a zeolite adsorption material containing a precious metal, the mass volume ratio of the precious metal in the zeolite adsorption material containing a precious metal to the carrier being 1-20 grams per cubic foot (0.0353-0.706 g:1 L), the mass volume ratio of the zeolite adsorption material containing a precious metal to the carrier being 200-280 g:1 L, and the mass content of the zeolite adsorption material containing a precious metal in the adsorption layer being 90-100%, The zeolite adsorption material containing a precious metal is obtained by exchanging a precious metal with a zeolite by an ion exchange method, that is, the zeolite adsorption material containing a precious metal is composed of the zeolite and a precious metal exchanged with the zeolite.
1. An ammonia adsorption catalyst comprising:
2. The precious metal comprises platinum and / or palladium; 2. The ammonia adsorption catalyst according to claim 1 .
3. The zeolite includes at least one of β zeolite, Y zeolite, and ZSM-5 zeolite.
3. The ammonia adsorption catalyst according to claim 1 or 2.
4. the support comprises at least one of cordierite, silicon carbide, and a metal support; 2. The ammonia adsorption catalyst according to claim 1 .
5. A method for producing the ammonia adsorption catalyst according to any one of claims 1 to 4, performing an ion exchange process on the zeolite using a precious metal precursor to obtain a precious metal-containing zeolite adsorbent material; mixing a zeolite adsorbent material containing precious metals with an adhesive and a solvent to produce a slurry; and coating the slurry on a carrier, drying and calcining the carrier to form an adsorption layer, thereby obtaining the ammonia adsorption catalyst.
2. The method for producing an ammonia adsorption catalyst comprising the steps of:
6. 5. Use of the ammonia adsorption catalyst according to any one of claims 1 to 4 for the adsorption and oxidation of ammonia in an engine aftertreatment system for engine exhaust treatment.
7. the engine aftertreatment system includes a stoichiometric engine aftertreatment system; 7. Use according to claim 6.
8. The engine aftertreatment system includes a three-way catalyst, and a gas to be treated in the engine aftertreatment system is first treated by the three-way catalyst and then treated by the ammonia adsorption catalyst; Alternatively, the engine aftertreatment system includes a selective catalytic reduction catalyst, and the gas to be treated in the engine aftertreatment system is first treated by the selective catalytic reduction catalyst and then treated by the ammonia adsorption catalyst. Use according to claim 6 or 7.
9. The ammonia adsorption catalyst is used in combination with a three-way catalyst using at least one of the following methods A and B: Method A: A three-way catalyst layer made of a three-way catalyst is provided between the adsorption layer of the ammonia adsorption catalyst and the carrier, Method B: The adsorption layer of the ammonia adsorption catalyst further contains the three-way catalyst; Use according to claim 6 or 7.
Citation Information
Patent Citations
Molecular sieve on carrier- palladium-platinum catalyst
JP1990174937A
Ammonia decomposing catalyst having denitration function and purification of exhaust gas
JP1993146634A
Exhaust gas cleaning catalyst
JP1997155199A
Exhaust purifying method and device therefor
JP1997173782A
Catalyst-carrying filter and exhaust gas cleaning system
JP2011104524A